Fenomena Hiperrealitas Anime Dikalangan Remaja Terhadap Identitas Warga Negara Indonesia ( Studi Kasus Komunitas Anime di Pontianak) - Bela Febriyanti; Sulistyarini; Syamsuri; Bistari; Atmaja, Thomy Sastra (CIVICS: Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2024)
ABSTRACT This study aims to determine the phenomenon of hyperreality towards the identity of Indonesian citizens, especially among teenage anime fans in Pontianak. The method used is a case study method with a qualitative approach. Data collection in this study used observation, interview and documentation techniques. The results of the study indicate that the form of hyperreality in the teenage anime community in Pontianak is in the form of cosplay activities, considering anime characters alive and real, the emergence of consumerism attitudes, and forgetting real life. The existence of the anime community in Pontianak also has positive impacts such as increasing piety to God Almighty, the growth of mutual cooperation attitudes, the existence of friendly attitudes, and increasing social awareness. Hyperreality in anime can indeed make someone have a new identity, but this identity cannot become part of the identity of the Indonesian nation because to become part of the Indonesian identity requires a long and complex process.